Aging evaluation of fuse holders of BWR nuclear power plant - Alejandra Armenta-Molina; Luis Héctor Hernández-Gómez; Carlos Daniel Pascual-Hernández; Daniel Villaseñor-Chávez; Gilberto Soto-Mendoza; Brayan Leonardo Pérez-Escobar; Tanya Nerina Arreola-Valles; Salatiel Pérez-Montejo (Results in Engineering)
The aging evaluation of a typical fuse holder, which is used in a BWR-5 nuclear plant, is discussed in this paper. This evaluation considered the guidelines of the NUREG-1760. A fuse holder, class R, has been considered. It has a wire gauge in the 500 kcmil – 4 Cu/Al range. It is used for a nominal current between 201 A and 400 A. It has 3 poles with a box-type terminal and a reinforcing clip, for blade-type fuses. The evaluation was carried out in two steps using the ANSYS® code. In the first, the operation of the fuse holder without aging was simulated. A three-dimensional model was used. The numerical solution requires the coupling of electrical, thermal, and mechanical analyses. It can be done with a single model. The mesh elements are Solid 232, Solid 291, and Solid 187. The model was refined at the clip holder and connector terminals. The model has 3,379,780 nodes and 2,387,463 elements. Its natural frequencies and the distribution of temperature, voltage, and stresses were obtained. The aging analysis was carried out in the second step after sixty years of operation. The loss of 1 mm in the thickness of the fastener, caused by corrosion or wear in the fuse assembly, was considered. The results showed that the vibration modes occurred with lower natural frequencies when inadequate contact occurred. Besides, changes in the other operating parameters were observed.